Management control and listing processes in SMEs: evidence from the apulian region - Ranaldo, Simona; Badia, Francesco; Dicuonzo, Grazia; Dell'Atti, Vittorio (Piccola Impresa / Small Business, 2021)
The widespread diffusion of SMEs within the Italian production system and their significant contribution to the country's economic growth makes it interesting to analyze the tools that encourage their development. Management control systems and listing processes represent two different tools that contribute to increasing the value of SMEs. Given the backwardness that characterizes the control systems implemented by SMEs and their lack of interest in the listing processes, this contribution intends to deepen these issues through an empirical analysis, considering the context of the Apulian SMEs, where there is currently only one company listed on the Italian stock exchange. The results show that although management control is widespread, there is little interest in starting quotation processes and knowledge of the recent facilitations introduced.